Peningkatan Kesadaran Mahasiswa dan Masyarakat dalam Menjaga Kebersihan Kawasan Sekitar Kampus - Muhammad Zakki; Dendi Maulana Dardiri; Mohamad Farid; Wakid Evendi; Suwito Suwito (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This article discusses efforts to increase student and community awareness in maintaining the cleanliness of the area around the Sunan Giri University Surabaya campus. Low initiative and collective responsibility were identified as the main problem in sanitation management in the campus buffer area, which resulted in the accumulation of waste in rivers, riverbanks, and the campus area. This community service activity used the Participatory Action Research (PAR) method, which was carried out in a collaborative cycle including problem mapping, action planning, activity implementation, and reflection. A total of 82 students, working together with the local community and Environmental Agency officers, were actively involved in river cleaning activities, removing water hyacinth, collecting organic and non-organic waste, and arranging the campus area. The results of the activities showed an increase in collective awareness of participants, characterized by the emergence of initiative, concern, and a sense of ownership of the environment. This improvement had a direct impact on the physical cleanliness of the area significantly, thus creating a healthier, more comfortable, and aesthetic environment. This community service activity concluded that the Participatory Action Research (PAR) method was effective in empowering communities, fostering a culture of environmental awareness, and developing sustainable hygiene habits. These findings provide an intervention model that can be replicated in other educational institutions to increase environmental awareness among the younger generation.